Application of machine learning in credit risk assessment: a prelude to smart banking - Dhruba, Mir Ishrak Maheer; Ghani, Nawab Haider; Hossain, Sazzad; Shoumo, Syed Zamil Hasan (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.